Respuestas
Respuesta dada por:
1
La ecuación que tienes es:
3 (x - 20) = x + 4
3x - 60 = x + 4
3x - x = 4 + 60
2x = 64
x = 64/2
x = 32
Respuesta.
x = 32
COMPROBAMOS LA SOLUCIÓN
3(x-20)= x+4
3 (32 - 20) = 32 + 4
3 (12) = 36
36 = 36
La solución es correcta!
3 (x - 20) = x + 4
3x - 60 = x + 4
3x - x = 4 + 60
2x = 64
x = 64/2
x = 32
Respuesta.
x = 32
COMPROBAMOS LA SOLUCIÓN
3(x-20)= x+4
3 (32 - 20) = 32 + 4
3 (12) = 36
36 = 36
La solución es correcta!
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años